Use of inhaled ciclesonide for treatment of moderate asthma in Thoroughbred racehorses - Macarena G. Sanz; Georgia Jellen; Lauren Cody; Jenyka Bergsma; Mandy Cha; Clark Kogan; Gordon Kordas; Warwick M. Bayly; Renaud Leguillette (Journal of Veterinary Internal Medicine)
Abstract Background Mild‐moderate asthma is common in horses. Inhaled ciclesonide has been approved only for treatment of severe asthma in horses. Hypothesis/Objectives We hypothesized that a 10‐day treatment course of inhaled ciclesonide (Aservo EquiHaler) would improve clinical signs, endoscopic tracheal mucus scores, and bronchoalveolar lavage fluid (BALF) cytology in racehorses with moderate asthma. Animals Racehorses with moderate asthma housed at the Emerald Downs Racetrack in Auburn, WA. Methods Prospective, randomized, double‐blinded, placebo‐controlled clinical study. Horses received inhaled ciclesonide (n = 12) or placebo (n = 9) for 10 days. Clinical signs were assessed at different times using the Tesarowski and HOARSI scores and cough during exercise. Endoscopy scoring, BALF cytology, and BALF cell selected gene expression (RT‐qPCR) were assessed on Days 0 and 10. Linear and ordinal simple and mixed effects models were used to analyze the data using R statistical software. Significance was set at P < .05. Results Only treated horses showed a decrease over time in HOARSI (P ≤ .001), cough (P = .001; −2.83 [−4.37, −1.29]), mast cell % (P = .03; −2.68 [−4.36, −1.0]) and relative expression of IL‐6 (P = .002; 0.44 [0.04, −6.99]) and IL‐13 (P = .03; 0.52 [0.04, −7.89]) in BAL cells. Treated horses had lower HOARSI (P = .002; −1 [1, 1]) and mast cell % (P = .02; −2.96 [−5.52, −0.39]) on Day 10. Conclusion and Clinical Importance Treatment with inhaled ciclesonide improved clinical signs and decreased BALF mastocytic inflammation in racehorses with moderate asthma without change in the environment. Treatment effect on neutrophilic or eosinophilic asthma remains undetermined. The small number of horses was a study limitation.